Pengembangan Bahan Ajar Interaktif ‘POST’ dalam Pembelajaran Apresiasi Puisi untuk Siswa Kelas X SMA - Nur Jamilah; Widyatmike Gede Mulawarman; Yusak Hudiyono (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
Poetry appreciation, one of the literature learnings in Senior High School (SMA), is a subject that has the most important part to establish students’ intuition and introduce literature as one of Indonesia's Cultures. Poetry appreciation teaching, which is one of the literature learnings given by teachers in the 2013 Curriculum nowadays, is expected to be the bridge that connects the students’ mindset and the learning purpose. This study is a kind of Research and Development. According to the study, the researcher finds some conclusions. First, the process of developing interactive teaching materials by using ‘POST’ audiovisual media product planning takes some steps (1) data researching and collecting, and (2) product planning, (3) product developing, (4) initial trial, (5) trial result revision, (6) field trial, (7) field trial result product improvement, (8) implementation field test, (9) final product improvement, (10) dissemination and implementation to produce learning CD as teaching materials. Second, the implementation of interactive teaching materials by using ‘POST’ audiovisual media application in poetry appreciation learning which produces CD is obtained through some process: (1) learning implementation, (2) observation, (3) questionnaire. Third, the product practicality of interactive teaching materials by using ‘POST’ audiovisual media is obtained from the score of lesson plan implementation analysis result which shows 93% and the students’ response seen from observation and questionnaire. Fourth, the product effectiveness of interactive teaching materials by using ‘POST’ audiovisual media is obtained from the advance individual trial score and the students’ activity.